Duke Ellington : the piano prince and his orchestra - Pinkney, Andrea Davis; Pinkney, J. Brian (New York : Hyperion Books for Children, 1998)
A brief recounting of the career of this jazz musician and composer who, along with his orchestra, created music that was beyond category.
Includes bibliographical references (p. [31]).
School Library Journal starred
Booklist starred
Pub Weekly
5.5
K-3
Keywords: Ellington, Duke, -- 1899-1974 -- Juvenile literature; Jazz musicians -- United States -- Biography -- Juvenile literature; Ellington, Duke, -- 1899-1974.; Musicians; Afro-Americans -- Biography; Ellington, Duke, -- 1899-1974.; Jazz musicians -- Biography; Musicians -- Biography; African Americans -- Biography